Neural crosstalk and symptom overlap: The correlation between urinary and intestinal symptoms in patients undergoing colonoscopy - Pedro Henrique P. Costa; Paulo Rodrigues; Lucas S. Takemura; Marina A. Germano; Mariane Ellen S. Sales; Gustavo A. de Paulo; Bianca Bianco; Maria Beatriz Lemos; Gustavo C. Lemos; Arie Carneiro (Investigative and Clinical Urology)
Purpose: Neural crosstalk in the pelvis involves intrinsic communication networks among pelvic structures that direct afferent inputs to converge on neurons, leading to viscerovisceral and somatovisceral reflexes. We aimed to explore the overlap between intestinal and urinary symptoms and their correlations in patients undergoing colonoscopy. Materials and Methods: Cross-sectional study with 167 participants who underwent colonoscopy and were assessed using three self-administered questionnaires: the International Prostate Symptom Score (IPSS) for lower urinary tract symptoms, the International Consultation on Incontinence Questionnaire Overactive Bladder (ICIQ-OAB) for overactive bladder symptoms, and the Gastrointestinal Symptom Rating Scale (GSRS) for gastrointestinal (GI) symptoms. Results: Among the participants, 55.1% were male, and the median age was 57 years. Most colonoscopies (80.8%) were performed for screening, and the most common finding was diverticular disease (DD) (35.9%). The IPSS and ICIQ-OAB were strongly correlated (rho=0.544, p<0.001), while the IPSS and GSRS scores showed a moderate correlation (rho=0.304, p<0.001). In the DD subgroup, both ICIQ-OAB and IPSS (rho=0.568, p<0.001), and IPSS and GSRS (rho=0.493, p<0.001) showed strong correlations. In contrast, the subgroup without DD showed a strong correlation between the ICIQ-OAB and IPSS (rho=0.510, p<0.001), but only a weak correlation between the IPSS and GSRS (rho=0.188, p=0.057), suggesting that the urinary-GI connection is influenced by the presence of DD. Conclusions: The findings revealed intrinsic relationships between urinary and GI symptoms, with DD as a significant factor influencing these relationships, suggesting that a more integrated approach to evaluate and manage these patients can potentially improve diagnostic accuracy and treatment outcomes.